Qualitative and Quantitative Determination of Secondary Metabolites and Antioxidant Potential of Leaf of Brahmi, Green Tea and Bulb of Onion Extracts - Dutta, Disha; Goyal, Naveen; Sharma, Dinesh Kumar (Journal of Drug Delivery and Therapeutics, 2019)
Utilization of herbs for medicinal purpose started in the early history of mankind several thousand years ago.In the last few years, there has been an exponential growth in the field of herbal medicine and gaining popularity both in developing and developed countries because of their natural origin and less side effects. Medicinal plants continue to be an important therapeutic aid for alleviating ailments of humankind. An antioxidant is a molecule capable of terminating the chain reactions that damage cells by removing free radical intermediates and inhibit other oxidation reactions by thereby reducing stress responsible for many degenerative disorders. The aim of the present study was to determine qualitative and quantitative phytochemical and in vitro antioxidant activities of leaf of Green tea, Brahmi and bulb of Onion collected from Bhopal region of Madhya Pradesh. Qualitative analysis of various phytochemical constituents and quantitative analysis of total phenol were determined by the well-known test protocol available in the literature. Quantitative analysis of phenolic content was carried out by Folins Ciocalteau reagent method. The in vitro antioxidant activity of methanolic extract of the leaf and bulb was assessed against DPPH assay method using standard protocols. Phytochemical analysis revealed the presence of phenols, flavonoids, tannins, saponins, alkaloids. The total phenolic content of leaf of Green tea, Brahmi and bulb of Onion was 195.26 ± 12.64, 136.92 ± 21.73 and 112.23 ± 11.36 mg/100mg respectively. The activities of methanolic leaves and bulbs extract against DPPH assay method were concentration dependent with IC 50 values of ascorbic acid and extracts 20.05±1.86 and 55.98±2.56, 104.45±3.13, 144.37±5.45μg/ml respectively. These studies provided information for correct identification of this plant material. The diverse array of phytochemicals present in the plant thus suggests its therapeutic potentials which may be explored in drug manufacturing industry as well as in traditional medicine. Keywords: Green Tea, Brahmi, Onion, Phytochemical constituents, Antioxidant activity